Feasibility Analysis of an Immersive Network Laboratory as a Support Tool for Teaching Practices - Erberson Evangelista Vieira; Francisco Petrônio de A. Medeiros (Journal on Interactive Systems)
Background: Information and Communication Technologies play a fundamental role in education, bringing real-world content closer to students and expanding learning opportunities. Immersive virtual laboratories stand out by enabling experimentation and overcoming the difficulties of accessing physical laboratories. Hybrid approaches have emerged to address challenges like space limitations, costs, and safety concerns in traditional laboratories by integrating immersive virtual environments with physical labs. The concept of the Metaverse is noteworthy for uniting physical and virtual realities, allowing user interaction through avatars. This combination aims to replicate the experience of in-person laboratories, fostering collaboration between students and teachers. The sense of presence in immersive virtual environments enhances realism, facilitating information processing during practical activities. This immersion can significantly benefit computing education, especially in laboratory-intensive subjects like Computer Networks that rely on physical equipment. Methods: In this context, this study aimed to investigate the use of immersive virtual environments as a support tool for teaching Computer Networks and to assess students’ acceptance of these environments as aids in teaching-learning. The methodology applied involved four phases: (1) a Systematic Literature Review, which identified research gaps and opportunities for new pedagogical practices in computing education, as well as reviewing related works; (2) semi-structured interviews with Computer Networks teachers, to support the immersive environment’s development; (3) modeling and development of the environment in the Metaverse; and (4) validation of environment acceptance using the Technology Acceptance Model (TAM) and the NASA Task Load Index. Results: The Systematic Review indicated that discussed pedagogical practices remain superficial, focusing on experimenting with existing environments and integrating the Metaverse with learning management systems (LMS). In Phase 2, the interviews revealed the importance of scalability in immersive virtual environments. The main goal of the interviews was to understand how teachers use computer and network laboratories, identifying the most-used equipment and content in teaching networks. This analysis was crucial for creating the interaction scenarios that guided the requirements of the NetVerse Edu platform. Conclusion: The acceptance results showed that students viewed NetVerse Edu as a valuable and effective tool for teaching networks, highlighting its ability to facilitate familiarization with equipment and understanding technical concepts. Regarding workload, the immersive environment proved challenging, requiring a high level of cognitive effort, but provided a productive experience without significant discomfort or frustration.